NFE2L3 as a Novel Biomarker Associated With IL-2/STAT5/NLRP3 Signaling Pathway in Malignant Pleural Mesothelioma and Other Cancers - Wang, Zhen; Yang, Han; Luo, Bin; Duan, Pengfei; Lin, Peng (Frontiers in Genetics, 2022)
Background Malignant pleural mesothelioma (MPM) is a malignant tumor originating from pleural mesothelial cells and has a high mortality rate worldwide. With the advent of immunotherapy in MPM treatment, there is an urgent need to elucidate the immune-related mechanisms in this caner. Methods Single-sample gene set enrichment analysis (ssGSEA) was used to score the immunocytes infiltration of data from different database sources. Identification of immunocyte-related genes was performed with weighted gene co-expression network analysis (WGCNA), differentially expressed genes (DEGs) analysis, and correlation analysis. Pan-caner analysis was performed using “DiffExp” and “Correlation” modules in TIMER. Results T-helper 2 (Th2) cell was found to be a poor prognostic factor for patients with MPM. Then a transcription factor, NFE2L3, was identified as a biomarker that showed a strong positive correlation with Th2 cell infiltration, and was highly expressed in MPM tissues and was related to the poor prognosis of these patients. At the same time, multiple NFE2L3 methylation sites were negatively correlated with Th2 cell infiltration, and patients with a high degree of methylation enjoy a better prognosis. Pan-caner analysis indicated that NFE2L3 might promote the differentiation of Th2 cells through the IL-2/STAT5/NLRP3 signaling pathway in MPM and many other cancers. Conclusion We believe that NFE2L3 can serve as a potential biomarker related to the diagnosis and prognosis of patients with MPM, and speculate that NFE2L3 could promote Th2 cell differentiation via IL-2/STAT5/NLRP3 signaling pathway in MPM and many other cancers.